2022
DOI: 10.3390/ijerph19095641
|View full text |Cite
|
Sign up to set email alerts
|

The Moral, Ethical, Personal, and Professional Challenges Faced by Physicians during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic, apart from the main problems concerning the health and life of patients, sparked a discussion about physicians’ moral and social professional attitudes. During a pandemic, physicians have the same ethical, moral, and medical responsibilities, however, the situation is different since they are self-exposed to a danger, which may influence their willingness to work. The problem of the professional moral attitudes of health care workers, recurring in ethical discussions, prompts us to defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The reasons behind refusal of medical attention or discharge against medical advice are manifold and complex, ranging from misunderstandings and language barriers to denial of illness, mistrust of the healthcare system, previous unpleasant experiences, fear, anger, and family obligations [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. It is vital for healthcare providers to understand these factors to better address them and provide optimal patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons behind refusal of medical attention or discharge against medical advice are manifold and complex, ranging from misunderstandings and language barriers to denial of illness, mistrust of the healthcare system, previous unpleasant experiences, fear, anger, and family obligations [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. It is vital for healthcare providers to understand these factors to better address them and provide optimal patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have investigated the extent to which the experience of violent events at work may increase the chances of burnout, including fear, anger, and depression [ 1 , 6 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] A recent study found that non-physical violence, mainly verbal aggression, was associated with emotional exhaustion, cynicism, and reduced professional efficacy [ 15 ]. Likewise, the participants in our study agreed that the assault had an emotional or physical impact on them, and it also impacted patients’ treatment and care.…”
Section: Discussionmentioning
confidence: 99%
“…This finding underscores the importance of the supervisory role in addressing legal issues and ensuring adherence to legal frameworks. [29][30][31][32] When comparing the results of this study with previously conducted research studies, several similarities and differences emerge. It is important to note that each study is influenced by unique contextual factors and sample characteristics, which may contribute to variations in findings.…”
mentioning
confidence: 94%